Jawabanmu

2014-08-18T20:09:08+07:00
Misal sisa = ax+b
x-1=0 , x=1 maka  a+b = -3
x + 1=0, x=-1 maka -a+b = 5

lalu eliminasilah a=-4 dan b = 1

maka sisa -4x+1
2014-08-18T20:18:48+07:00
F(-1) = -3
f(1) = 5
f(x) = (x^2-1)(H(x)) + ax +b
     = (x-1)(x+1) (H(x)) + ax + b
f(-1)=(-1-1)(-1+1)(H(x)) + a(-1) + b = -3
     = (-2)(0) (H(x)) -a + b = -3
     = -a + b = -3
f(1)=(1-1)(1+1)(H(x)) + a(1) +b = 5
     = (0)(2)(H(x)) + a + b = 5
     = a +b =5
eliminasi
-a+b = -3
a+b = 5
__________-
-2a= -8
a = 4
substitusikan
a+b=5
4+b=5
   b= 5 - 4
   b = 1
maka sisa pembagian
4x+1

maaf kalau salah....